A critical evaluation of developmental local government in the City of Johannesburg, 2001-2005 - Seedat, Rashid Ahamed (My University, 2009)
A critical evaluation of developmental local government in the City of Johannesburg, 2001-2005 is a qualitative analysis drawn from participation in setting, interviews and primary and secondary sources. It notes that the notion of developmental local government is drawn from a wide range of discourses such as developmentalism, decentralised local government, public management, governance, urban fragmentation and integration and sustainable development. The study takes the view that the notion of developmental local government would be more concisely conceptualised in terms of and as a confluence of the concepts of good governance, urban integration and sustainable development. These concepts are used to frame and critically analyse the practise of developmental local government in the City of Johannesburg between 2001-2005. The overall conclusion of the study is that the City of Johannesburg has embraced developmental local government between 2001-2005, albeit with some deficiencies, mainly relating to the gap between policy and implementation.
Keywords: local government; municipalities; Johannesburg; governance; cities; urban fragmentation; urban integration; urban planning; development